A numerical approach for solving singular nonlinear LaneEmden type equations arising in astrophysics - Nasab, Aliasghar Kazemi; Kilicman, Adem; Atabakan, Z. Pashazadeh; Leong, Wah June (Elsevier, 2015)
In this paper, we suggest a numerical method based upon hybrid of Chebyshev wavelets and finite difference methods for solving well-known nonlinear initial-value problems of Lane–Emden type. The useful properties of the Chebyshev wavelets and finite difference method are utilized to reduce the computation of the problem to a set of nonlinear algebraic equations. Making a comparison among the obtained results using the present method with those ones reported in literature by some other well-known methods confirms the accuracy and computational efficiency of the present technique.